(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
Ancient and medieval Kyrgyz people worshiped Kok Tegir, Umai Ene (cult of the mother Umai), Yer-Sub (Earth-Water). During the Middle Ages, the Kyrgyz in general remained shamanists, whose cults arose in the conditions of the clan structure long before the formation of their state. In addition, elements of other world religions were present in the philosophical and religious environment of the Kyrgyz society: Buddhism, Zoroastrianism, Manicheism, Eastern Christianity (Nestorianism). Despite the presence of the spirit of the ancestors, in contrast to the Turks and Polovtsians (Kuman-Kipchaks), the custom of erecting stone statues in honor of their ancestors did not become widespread among the Kyrgyz. The Kyrgyz were fire worshipers. The fire goddess “Ot-Ine” gives warmth and light, guards the home and family from evil forces around the clock, brings luck and wealth to the owner, lives by the care of the head of the house. Each Kyrgyz clan also worshiped certain types of trees, which were considered the guardians of ancestral souls. In the Kyrgyz society, clergymen were called «kam», in Arabic sources «faginun» («fahginun»), bögү («bögü»).